Quality Standard and Specification for Soft-scape Construction in Malaysia - Ab Sani, Jasasikin; Othman, Noriah (Elsevier, 2012)
This paper reviews the status of soft-scape construction quality standards in Malaysia. Quality standard documents from related government agencies and selected private company in Malaysia had been collected for comparison. Comparison has been made on every item in quality standard from 3 parties involved to identify the similarities and differences. The study found that the content structures in documents from three parties are different in terms of number of headings and sub-heading, title of heading and sub-heading. There are also inconsistencies in descriptions of the topic from all three standard specifications.